Geological and geotechnical research model to define the foundation of electrical transmission line structures - Lovera, Epifanio Suyo Rivera (2016)
998/5000       This work explains the need for a geological and geotechnical research model to define the foundation for structures (towers and poles) of electric transmission lines. In practical engineering, it has been found that in some project studies of this type, geological investigations are diminished or dispensed with, thereby damaging geotechnical investigations based on knowledge of geological sciences. Because of this there is also less confidence in stability and security for future works to be built. With this research, the methodologies of geological and geotechnical investigations are broadly exposed, and a tentative general model of geological and geotechnical investigations to define the foundation of the structures of electric transmission lines is presented. In addition, an example of application made by the author in the Orcopampa mining area in Arequipa in 2005 is presented.